Manchester Arena bombing: lessons learnt from a mass casualty incident. Issue 2 (6th April 2018) - Craigie, Ross J; Farrelly, P J; Santos, R; Smith, S R; Pollard, J S; Jones, D J
Abstract : On 22 May 2017 Salman Abedi detonated an improvised explosive device in the Manchester Arena resulting in 23 deaths (including the attacker). This was the deadliest terrorist attack on UK soil since the 2005 London bombings, but was only one of five mass casualty terrorist attacks in the UK in 2017. Preparation for mass casualty incidents (MCI) is obligatory, involving such methods as multiagency tabletop exercises, mock hospital exercises, as well as simulation and training for clinicians in managing the injuries that would be anticipated in such an event. Even in the best prepared units, such an incident will pose significant challenges due to the unpredictable nature of these events with respect to timing and number of casualties. Following an MCI, local and national reviews are undertaken to assess the effectiveness of the response, but also to identify areas where lessons can be learnt and to disseminate these to allow inclusion in future planning. We present the experience following a mass casualty terrorist incident along with a number of lessons learnt from this event.